Analysis of Data Aggregates of Social Demography - Atmoko Nugroho (Universitas Kristen Satya Wacana, 2023)
Social demographics in an area are often displayed in the form of aggregate data for all those who want social demographic data. But often the components displayed are not uniform between one region and another, after all, the relationship between the components is not explained. Therefore, the analysis is needed to determine the interrelationships between the components and to test the aggregate data that is displayed.